Green Building, Sustainability and Mosques Design in Kuala Terengganu - Mat Sharif, Zainon; Jannah Jalil, Nurul; Ali Bekhet, Hussain (International Journal of Engineering and Technology, 2019)
The purposes of this study were to identify, determine and investigate the green building technology, factors influenced the mosques design and facilities provided for the disable in every mosque towards the sustainability of the mosques. The study employs exploratory and observation design with qualitative approach, to the selected mosques in Kuala Terengganu. The study reveals about the basis of equality within the Muslim society which are equitably and protective treatment of the rights of every individual regardless of their physical ability or disability. Basis of equality is referring to the act of considering about the complications faced by others and the act of providing easy and safe access for the public. As concern, the modern mosque design build with moderate use of resources, energy, and space development as the environmental cognizant design technique will benefit to the Muslim society. The empirical findings in this study will improve the efficiency usage of space in religious building and minimize the negative environmental impact produced by applying this concept of green building sustainability. Hence, functional quality of mosque’s architectural space and building design can be constructed for Muslim community use.